Disconnect between adipose tissue inflammation and cardiometabolic dysfunction in Ossabaw pigs. (2nd November 2015) - Vieira‐Potter, Victoria J.; Lee, Sewon; Bayless, David S.; Scroggins, Rebecca J.; Welly, Rebecca J.; Fleming, Nicholas J.; Smith, Thomas N.; Meers, Grace M.; Hill, Michael A.; Rector, R. Scott; Padilla, Jaume
Abstract : Objective: The Ossabaw pig is emerging as an attractive model of human cardiometabolic disease because of its size and susceptibility to atherosclerosis, among other characteristics. The relationship between adipose tissue inflammation and metabolic dysfunction in this model was investigated here. Methods: Young female Ossabaw pigs were fed a Western‐style high‐fat diet (HFD) ( n  = 4) or control low‐fat diet (LFD) ( n  = 4) for a period of 9 months and compared for cardiometabolic outcomes and adipose tissue inflammation. Results: The HFD‐fed "OBESE" pigs were 2.5 times heavier ( P  < 0.001) than LFD‐fed "LEAN" pigs and developed severe obesity. HFD feeding caused pronounced dyslipidemia, hypertension, and insulin resistance (systemic and adipose), as well as induction of inflammatory genes, impairments in vasomotor reactivity to insulin, and atherosclerosis in the coronary arteries. Remarkably, visceral, subcutaneous, and perivascular adipose tissue inflammation (via FACS analysis and RT‐PCR) was not increased in OBESE pigs, nor were circulating inflammatory cytokines. Conclusions: These findings reveal a disconnect between adipose tissue inflammation and cardiometabolic dysfunction induced by Western diet feeding in the Ossabaw pig model.